Melatonin Induces per1a Expression in Zebrafish Brain - Cher Ryn Lim; Zhen Xuen Brandon Low; Tomoko Sogo; Yatinesh Kumari (Progress in Microbes and Molecular Biology)
In vertebrates, the circadian mechanism regulates many physiological and behavioral activities. The major key output of the circadian clock is the secretion of melatonin in the pineal gland. Melatonin secretion remains low during the daytime and increases significantly at night. The rise and fall of melatonin level is a key factor that conveys rhythmic information to the organism to carry out daily and annual physiological rhythms. It also affects the rhythmic oscillation of clock genes in the suprachiasmatic nucleus (SCN) as well as in peripheral tissues. In this study, we have shown that zebrafish brain rhythmically expresses per1a and cry1a in different photoperiodic regimes: light-dark cycle (LD) and continuous light (LL). We have also demonstrated that an acute injection of melatonin in the middle of the subjective day induces per1a expression in zebrafish brain. Furthermore, we have also shown that an acute injection of melatonin affects circadian regulation of locomotor activity in zebrafish under LD conditions. These results provide insight into understanding the underlying mechanism of melatonin in regulation of clock genes and locomotor activity in zebrafish.